Financial Administration of Information Systems Regional Government at The Regional Secretariat of Minahasa Regency - Wurangian, Anjastyo; Wawointana, Thelma; Mamonto, Fitri H. (Technium Social Sciences Journal, 2024)
This research aims to determine the Financial Administration of the Regional Government Information System at the Regional Secretariat of Minahasa Regency. This research uses a descriptive method with a qualitative approach. Data collection techniques include observation, interviews and documentation methods. Data processing techniques with stages of data reduction, data presentation and verification. This research highlights the Financial Administration of Regional Government Information Systems (SIPD) at the Regional Secretariat, both in the aspects of budget planning and budgeting. Planning is carried out using the Strategy Formulation, Work Control, and Monitoring Management processes, while budgeting is carried out based on the Work Guidelines, Coordination Tools, and Monitoring processes. so that there are obstacles in planning, namely planning efficiency, facilities and infrastructure, and readiness to use SIPD, as well as obstacles in budgeting, namely employee transfers, human resources, and the expenditure filing process which are factors inhibiting the SIPD financial administration process at the Regional Secretariat of Minahasa Regency. Based on the results of the research conducted, it can be concluded that the SIPD Financial Administration at the Regional Secretariat has been running well even though there are still many obstacles. It is recommended that the Regional Government increase the capacity of Human Resources, repair and increase supporting facilities and infrastructure, and for the Central Government to perfect the SIPD application.